FRAZEOLOGIK BIRLIKLAR MILLIY TILNING LEKSIK BOYLIGIDIR («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article discusses phraseological units in a language, its domain. The concepts of phraseological units are given in different languages   using various terms and interpretations, which can be based on many lexical units.
Keywords: phraseological units, areas, terms, interpretations, lexical units, idioms, proverbs, writers' aphorisms, winged words, national traits.